THE POLITICAL PARTICIPATION OF YOUTH AND THE PROMOTION OF VOTER REGISTRATION (CIPEEX, 2025)
The political participation of young people is essential for renewing democratic institutions and strengthening social rights. However, recent data indicate a growing disinterest in politics among youth, reflected in the decline of voter registration and reduced presence at the polls. This scenario raises concerns about the representativeness and legitimacy of future elected governments.Therefore, this study aims to analyze the importance of civic education and the promotion of political awareness as means to encourage youth participation in the electoral process. The methodology adopted consisted of a literature review, with critical analysis of academic articles, institutional reports, and statistical data on youth voting behavior, including reports from the Superior Electoral Court (TSE) and institutional campaigns carried out between 2018 and 2024.The results show that educational initiatives such as school debates, mock election projects, and voter registration incentive programs can generate greater interest and understanding among young people regarding their role in democracy. In addition, specific public policies that bring youth closer to political institutions—such as awareness campaigns promoted by the Electoral Justice—also significantly contribute to reversing political disengagement.It is concluded that continuous political education, starting from basic education and combined with modern and accessible communication strategies, is fundamental to awakening a sense of civic responsibility among young people. This promotes conscious and critical engagement in voting and other forms of political participation. Strengthening democracy requires valuing and actively including young people in collective decision-making processes.
Keywords: youth; political participation; voter registration; civic education; democracy